Examination of the relationship between compulsive online shopping behavior and depression, anxiety, and stress - Traş, Zeliha; Yakıcı, Hikmet Beyza (Journal of Dependence, 2023)
Objective: The aim of this study is to examine the relationship between compulsive online shopping behavior with depression, anxiety, and stress in individuals. It also examined whether compulsive online shopping behavior differs according to gender and perceived income level. Method: A correlational survey model was used. The study group consisted of a total of 385 participants, 93 men (24.2%) and 292 women (75.8%) who were 18 years of age and older (=26.12, sd=4.54) and were engaged in online shopping behavior. Compulsive Online Shopping Behavior Scale and Depression, Anxiety, Stress Scale and Personal İnformation Form were used as data collection tools. Results: Compulsive online shopping behavior of individuals did not differ according to gender. A moderately positive and significant relationship was obtained between the individuals’ compulsive online shopping behavior scores and their depression, anxiety, and stress sub-dimensions scores. Depression, anxiety, and stress sub-dimension scores explain 17% of the total variance in compulsive online shopping behavior. Conclusion: Compulsive online shopping behavior varies by gender. The increase in depression, anxiety, and stress levels of individuals increases compulsive online shopping behaviors.